Do Fetal Isolated Mild Venticulomegaly Make Any Difference in Regional ADC Values at Magnetic Resonans Imaging? - Zeynep Ayvat Öcal; Özgür Öztekin; Deniz Oztekin (Galenos Publishing House, 2021)
Objective: Ventriculomegaly may not only develop secondary to a process,but it may also be in the form of isolated ventriculomegaly with no specific reason. MRI is performed to show the presence of accompanying pathologies.In this study, we measured ADC values in mild ventriculomegaly cases and aimed to investigate the role of ADC value measurements in predicting neurological prognosis in isolated mild ventriculomegaly during MRI. Methods: In our study, ADC values were measured of 37 patients detected to be present with mild ventriculomegaly and 17 fetuses in the control group who had no additional central nervous system patology. For the measurement, ROI was placed in differtent brain regions (frontal lobe white matter,occipital lobe white matter, basal ganglia, thalamus, cerebellum and pons). The analysis of the data obtained was performed using the SPSS (20th version) program. MannWhitney U test was applied. Statistical significance level was set as p<0.05. Results: There was no statistically significant difference between the isolated mild ventriculomegaly and the control group in terms of the mean maternal age (p=0.160). Also, no statistically significant difference was observed between the mean gestational age in the ventriculomegaly group and the control group (p=0.890). There was also no statistically significant difference between ADC measurements in different brain regions in the isolated mild ventriculomegaly and the control group (p=0.807). Conclusion: In order to determine the prognosis in isolated mild ventriculomegaly, other quantitative parameters such as ADC measurement, beyond morphological evaluation and diameter measurement should be determined, and also we need more studies comprising more cases in this field.